Therapeutic itineraries and explanations for tuberculosis: an indigenous perspective - Laura Maria Vidal Nogueira; Elizabeth Teixeira; Paulo Cesar Basta; Maria Catarina Salvador da Motta (Universidade de São Paulo, 2015)
ABSTRACT OBJECTIVE To analyze explanations for tuberculosis and therapeutic itineraries of Brazilian indigenous people. METHODS Case study with a qualitative-descriptive approach. We conducted semi-structured interviews with 11 Munduruku indigenous, including direct observation of treatment for tuberculosis in the municipality of Jacareacanga, south-western region of the state of Para, Brazil. To identify explanations for tuberculosis and therapeutic itineraries, we performed thematic content analysis. RESULTS Traditional medicine was the first therapeutic option chosen by the indigenous. However, biomedicine was also employed, which indicates a circulation between different therapeutic contexts and health concepts among the Munduruku. The explanations provided ranged from recognition of the signs and symptoms specific to tuberculosis to the attribution of the disease to a spirit that leaves the body and wanders in the woods, returning ill into the body. Unlike the biomedical model, which links tuberculosis transmission strictly to interpersonal contact, in closed spaces without natural lighting and ventilation (preferably domestic environments), the Munduruku associate the disease to an indirect contact between people socially distant (enemies or adversaries) in public and open places. CONCLUSIONS The explanations made by the indigenous are unique and deserve the attention of those who are responsible for developing health public policies, as well as of the teams who work on the villages. To guarantee an efficient control of tuberculosis in these regions, it is necessary that the developed actions integrate biomedicine knowledge and the traditional medicine of the indigenous people, in addition to respecting and welcoming local culture manifestations.